Effect of different pre-irradiation times on curcumin-mediated photodynamic therapy against planktonic cultures and biofilms of Candida spp - Andrade, Mariana Carvalho [UNESP]; Ribeiro, Ana Paula Dias; Dovigo, Lívia Nordi [UNESP]; Brunetti, Iguatemy Lourenço [UNESP]; Giampaolo, Eunice Teresinha [UNESP]; Bagnato, Vanderlei Salvador; Pavarina, Ana Claudia [UNESP] (Elsevier, 2013)
Objectives: The aim of this study was to evaluate the effects of pre-irradiation time (PIT) on curcumin (Cur)-mediated photodynamic therapy (PDT) against planktonic and biofilm cultures of reference strains of Candida albicans, Candida glabrata and Candida dubliniensis. Materials and methods: Suspensions and biofilms of Candida species were maintained in contact with different concentrations of Cur for time intervals of 1, 5, 10 and 20 min before irradiation and LED (light emitting diode) activation. Additional samples were treated only with Cur, without illumination, or only with light, without Cur. Control samples received neither light nor Cur. After PDT, suspensions were plated on Sabouraud Dextrose Agar, while biofilm results were obtained using the XTT-salt reduction method. Confocal Laser Scanning Microscopy (CLSM) observations were performed to supply a better understanding of Cur penetration through the biofilms after 5 and 20 min of contact with the cultures. Results: Different PITs showed no statistical differences in Cur-mediated PDT of Candida spp. cell suspensions. There was complete inactivation of the three Candida species with the association of 20.0 μM Cur after 5, 10 and 20 min of PIT. Biofilm cultures showed significant reduction in cell viability after PDT. In general, the three Candida species evaluated in this study suffered higher reductions in cell viability with the association of 40.0 μM Cur and 20 min of PIT. Additionally, CLSM observations showed different intensities of fluorescence emissions after 5 and 20 min of incubation. Conclusion: Photoinactivation of planktonic cultures was not PIT-dependent. PIT-dependence of the biofilm cultures differed among the species evaluated. Also, CLSM observations confirmed the need of higher time intervals for the Cur to penetrate biofilm structures. © 2012 Elsevier Ltd. All rights reserved.
Keywords: Biofilms; Candida; Curcumin; Drug resistance; Photochemotherapy; Candida albicans; Candida dubliniensis; Candida glabrata